Isoform switch of CD44 induces different chemotactic and tumorigenic ability in gallbladder cancer - Miwa, Takeshi (Int J Oncol, 2017)
Gallbladder cancer (GBC) is one of the most unfavorable prognostic tumor, and immediate growth and distant metastasis are important factors associated with the poor prognosis of patients with this disease. Standard and variant isoforms of CD44 are associated with tumor growth, metastasis, and epithelial-mesenchymal transition (EMT), although their roles in GBC are unclear. We investigated the relationship between the CD44 isoforms with EMT, chemotaxis, and tumorigenicity. We analyzed CD44 expression in the GBC cell line NOZ and found that it comprises a major population that expressed CD44std(+)/CD44v9(−) (CD44s) and the minor population that expressed CD44std(−)/CD44v9(+) (CD44v). CD44s cells exhibited increased chemotaxis and invasiveness compared with CD44v cells in in vitro cell migration and invasion assays. CD44s cells expressed higher and lower levels of mRNAs that encode vimentin and E-cadherin, respectively, compared with those of CD44v cells. CD44s cells expressed high levels of the transcription factors ZEB1 and ZEB2 that mediate EMT, and low levels of a splicing factor ESRP1 that controls the CD44 isoform switch. We performed in vivo mouse xenotransplantation analyses of CD44s and CD44v cells and found that CD44v cells exhibited relatively increased tumorigenicity. Immunohistochemical analysis of tissue microarrays revealed that high levels of CD44v9 and CD44std were associated with poorer prognosis. The expression of CD44std was also associated with poorly differentiated tumors and distant metastasis. In conclusion, CD44s was associated with a mesenchymal phenotype, increased chemotaxis and invasiveness, and decreased tumorigenicity. In contrast, CD44v cells exhibited an epithelial phenotype, decreased chemotaxis, decreased invasiveness, and increased tumorigenicity. These findings suggest that CD44v and CD44s cells play differently important roles in the progression and metastasis of GBC and the isoform switch triggers EMT.